KEBENARAN ILMIAH DALAM HUKUM - Irma Nur Hayati (Fakultas Agama Islam Universitas Nurul Jadid, 2021)
According to Michael Williams, there are five theoretical formulations of truth: Correspondence Truth, Coherence Truth, Pragmatic Truth, Performative Truth, and Propositional Truth. In the history of Western philosophy, actual knowledge corresponds to reality, while in Eastern philosophy, proper knowledge is the knowledge that saves. There are three Institutes of Truth, namely: Science, Philosophy, and Religion, all of which have points of similarity on the one hand and issues of difference on the other. The topics of similarity include: Neither Science nor Philosophy nor Religion aim at least the same thing: Truth. With their respective characteristics, Science, philosophy, and Religion seek the truth about nature and include humans and God. The points of difference, including Both Science and Philosophy, both result from the same source, namely human reason, while Religion comes from divine revelation. Both Science and Philosophy begin with an attitude of doubt or disbelief. Religion begins with an attitude of trust and faith. Both the truth of Science, and the fact of Philosophy, are relative (relative). At the same time, the reality of Religion is absolute (absolute) because Religion is a revelation sent down by the One Who is True, Absolute, and Perfect.